2009
DOI: 10.1002/vnl.20194
|View full text |Cite
|
Sign up to set email alerts
|

Silane grafting and moisture crosslinking of polyethylene: The effect of molecular structure

Abstract: The silane grafting and moisture crosslinking of different grades of polyethylene have been investigated. Three types of polyethylene (HDPE, LLDPE, and LDPE) with different molecular structures and similar melt flow indices were selected. The initiator was dicumyl peroxide (DCP), and the silane was vinyltrimethoxysilane. The grafting reaction was carried out in an internal mixer. The extent of grafting and the degree of crosslinking were determined, and hot-set tests were carried out to evaluate the crosslink … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 17 publications
0
14
0
1
Order By: Relevance
“…The molecular structure of a PE is an important characteristic influencing the physical and chemical properties. It has been reported that the structural parameters such as number average molecular weight, the molecular weight distribution, the presence of unsaturated functional groups (vinyl groups), and the content of branches as well as their length had important effects in the crosslinking/grafting behavior of PEs 20–23…”
Section: Introductionmentioning
confidence: 99%
“…The molecular structure of a PE is an important characteristic influencing the physical and chemical properties. It has been reported that the structural parameters such as number average molecular weight, the molecular weight distribution, the presence of unsaturated functional groups (vinyl groups), and the content of branches as well as their length had important effects in the crosslinking/grafting behavior of PEs 20–23…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, it was shown that the rate of crosslinking for LDPE is higher than those of LLDPE and HDPE because of lower crystallinity. 31 The lower gel content for HDPE may be attributed to the …”
mentioning
confidence: 99%
“…Different substances, such as peroxides [7], silanes [8][9][10] or ionizing radiations [11][12][13][14], are regularly used as crosslinking agents. The resulted crosslinked materials have widely applied in cable industry due to their excellent dielectric properties, better water-tree resistance and suitable thermo-mechanical behavior [5,15]. However, the long-term performances of these materials are affected by oxidative degradation which is induced by combined environmental actions (heat transfer, photooxidative or high energy radiation exposures, mechanical loadings) which have energy transfer reasons usually accompanied by electrical stresses during the service life.…”
Section: Introductionmentioning
confidence: 99%